Civil Liberties in the Midst of the Threat of Disinformation: Protests and Constitutional Law Challenges in the Post-Truth Era - Aringga, Rino Dedi; Meuraksa, M. Amin El-Walad (Abdurrauf Social Science, 2025)
This study addresses the growing problem of disinformation in the digital public sphere, which directly affects civil liberties, particularly the right to express opinions through demonstrations. Disinformation in the post-truth era not only intensifies social polarization but also poses new challenges for constitutional law in balancing the protection of fundamental rights and public order. The objective of this research is to analyze the impact of the post-truth era on civil liberties and to examine the implications of constitutional law in regulating demonstrations amid the threat of disinformation. The study applies a normative juridical method with a conceptual and statutory approach, using primary sources such as the 1945 Constitution, Law No. 9 of 1998, the Electronic Information and Transactions Law, and Constitutional Court decisions, complemented by secondary sources including academic literature on disinformation and democracy. The findings reveal that the post-truth era shifts the meaning of civil liberties by prioritizing subjective opinions over facts, leading to the restriction of public expression. Inconsistencies in regulations and weak legal instruments exacerbate constitutional challenges in addressing this issue. The implications highlight the urgency of reformulating balanced and adaptive regulations to respond to digital dynamics, ensuring the protection of civil liberties while preventing the harmful effects of disinformation. Abstrak: Penelitian ini berangkat dari persoalan meningkatnya praktik disinformasi di ruang publik digital yang berimplikasi langsung terhadap kebebasan sipil, khususnya hak menyampaikan pendapat melalui unjuk rasa. Disinformasi yang berkembang di era post-truth tidak hanya menimbulkan polarisasi sosial, tetapi juga menghadirkan tantangan baru bagi hukum tata negara dalam menjaga keseimbangan antara perlindungan hak fundamental dan ketertiban umum. Tujuan penelitian ini adalah menganalisis pengaruh era post-truth terhadap kebebasan sipil dan menelaah implikasi hukum tata negara dalam mengatur unjuk rasa di tengah ancaman disinformasi. Metode yang digunakan adalah yuridis-normatif dengan pendekatan konseptual dan perundang-undangan, menggunakan sumber data primer berupa UUD 1945, UU No. 9 Tahun 1998, UU ITE, serta putusan Mahkamah Konstitusi, dan sumber sekunder berupa literatur akademik terkait disinformasi dan demokrasi. Hasil penelitian menunjukkan bahwa era post-truth menggeser makna kebebasan sipil dengan menempatkan opini subjektif di atas fakta, yang berdampak pada pembatasan ruang berekspresi. Inkonsistensi regulasi dan lemahnya instrumen hukum memperkuat tantangan hukum tata negara dalam merespons fenomena ini. Implikasi penelitian menegaskan perlunya reformulasi regulasi yang seimbang, adaptif, dan kontekstual terhadap dinamika digital, agar kebebasan sipil tetap terjamin tanpa mengabaikan kebutuhan pencegahan disinformasi.